“CHALLENGES AND SOLUTIONS IN USING MOBILE APPLICATIONS FOR TEACHING BUSINESS ENGLISH IN HIGHER EDUCATION” - Barchinoy Sultanova Davronovna; Farangiz Nurmamatova Irkinovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the opportunities, challenges, and solutions of using mobile applications in teaching Business English in higher education. It highlights ways to enhance learning effectiveness through the MALL approach. In addition, the study examines the experience of TSUE and the role of popular mobile apps such as ELSA Speak, Grammarly, and others, with an emphasis on developing learners’ communicative competence.